Characteristics and Sources of Intense Geoelectric Fields in the United States: Comparative Analysis of Multiple Geomagnetic Storms. Issue 4 (19th April 2022) - Shi, Xueling; Hartinger, Michael D.; Baker, Joseph B. H.; Murphy, Benjamin S.; Bedrosian, Paul A.; Kelbert, Anna; Rigler, Erin Joshua
Abstract: Intense geoelectric fields during geomagnetic storms drive geomagnetically induced currents in power grids and other infrastructure, yet there are limited direct measurements of these storm‐time geoelectric fields. Moreover, most previous studies examining storm‐time geoelectric fields focused on single events or small geographic regions, making it difficult to determine the typical source(s) of intense geoelectric fields. We perform the first comparative analysis of (a) the sources of intense geoelectric fields over multiple geomagnetic storms, (b) using 1‐s cadence geoelectric field measurements made at (c) magnetotelluric survey sites distributed widely across the United States. Temporally localized intense perturbations in measured geoelectric fields with prominences (a measure of the relative amplitude of geoelectric field enhancement above the surrounding signal) of at least 500 mV/km were detected during geomagnetic storms with Dst minima ( Dst min ) of less than −100 nT from 2006 to 2019. Most of the intense geoelectric fields were observed in resistive regions with magnetic latitudes greater than 55° even though we have 167 sites located at lower latitudes during geomagnetic storms of −200  nT  ≤  Dst min < −100  nT . Our study indicates intense short‐lived (<1 min) and geoelectric field perturbations with periods on the order of 1–2 min are common. Most of these perturbations cannot be resolved with 1‐min data because they correspond to higher frequency or impulsive phenomena that vary on timescales shorter than that sampling interval. The sources of geomagnetic perturbations inducing these intense geoelectric fields include interplanetary shocks, interplanetary magnetic field turnings, substorms, and ultralow frequency waves. Plain Language Summary: Geomagnetic perturbations related to various phenomena in the near‐Earth space environment can induce geoelectric fields within the electrically conducting Earth. The geoelectric field is an important link between phenomena in geospace and geomagnetically induced currents in grounded electricity transmission networks. To investigate sources of hazardous geoelectric fields during geomagnetic storms, we use 1‐s geoelectric field measurements that are distributed across the United States. Temporally localized intense perturbations in measured geoelectric fields with prominences of at least 500 mV/km were detected during geomagnetic storms with a Dst minimum of less than −100 nT from 2006 to 2019. Most of these perturbations cannot be resolved with 1‐min data because they correspond to phenomena that vary on smaller timescales and higher frequencies. Characteristics and sources of these intense geoelectric fields across multiple geomagnetic storms and multiple geographic regions are investigated. Key Points: First multi‐storm and multi‐station comparative analysis of intense geoelectric fields measured at 1 s cadence Interplanetary shocks, ultralow frequency waves, substorms, and interplanetary magnetic field turnings are common sources of intense geoelectric fields The causes of intense geoelectric fields differ from storm to storm due to dependence on multiple factors